Determinan Sosial Pernikahan Dini pada Perempuan di Kecamatan Jerowaru di Kabupaten Lombok Timur - Riadatul Jannah (Pusat Riset dan Inovasi Nasional, 2023)
Early marriage refers to marriages in which both partners are aged 18 and under or those who are not ready to marry due to various factors, such as the level of physical, emotional, sexual and psychosocial development, or lack of information regarding one's life choices. Women who marry early are blamed by various factors such as economic level, educational level, social culture, and premarital sex. The purpose of this research is to explore the determinant of early marriage among adolescent women. This research method uses a descriptive with a qualitative approach. The subjects of this study were women aged 12-18 years who married early and their families. The data collection technique used is in-depth interviews. Analysis data begins with determining the coding, categories and themes which are then interpreted using NVivo 12 Plus. The results of this study indicate that the women who marry early are caused by economic level, parents' education, girl’s education, customs and traditions in society, parents' divorce, and the influence of social media.